BIOSYNTHESIS OF IRON OXIDE NANOPARTICLES USING HYDROCOTYLE UMBELLATA L. AND ITS ANTIDIABETIC AND ANTIOXIDANT ACTIVITY - SULOCHANA GOVINDHARAJ; KOHILA KALIMUTHU; KANISH S; RAJESHKUMAR SHANMUGAM (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: The objective of the present study was to synthesize iron oxide nanoparticles (Fe2O3 nanoparticles [NPs]) using Hydrocotyle umbellata L. through a biogenic approach and to evaluate their antidiabetic potential through α-amylase and α-glucosidase inhibitory assays, along with antioxidant activity using 2,2-Diphenyl-1-picrylhydrazyl (DPPH), H2O2, Ferric reducing antioxidant power (FRAP), 2,2’-azino-bis(3-ethylbenzothiazoline-6- sulfonic acid) ABTS, and nitric oxide scavenging assays. Methods: Iron oxide nanoparticles were synthesized using H. umbellata L. extract and characterized by ultraviolet (UV)-visible spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy analysis. The antioxidant efficacy of the synthesized nanoparticles was evaluated using DPPH, hydrogen peroxide (H2O2), FRAP, ABTS, and nitric oxide assays. Antidiabetic activity was assessed through α-amylase and α-glucosidase inhibitory assays at different concentrations (10–50 μg/mL), and results were compared with standard antioxidants and antidiabetic drugs. Results: The formation of Fe2O3 NPs was confirmed by UV-visible spectroscopy, showing a characteristic absorption peak at 440 nm after 48 h. The synthesized nanoparticles exhibited strong antioxidant activity, with DPPH radical scavenging activity ranging from 63.55% to 88.32% at concentrations of 10–50 μg/mL, comparable to the standard ascorbic acid. Significant α-amylase inhibitory activity (48–84%) was observed when compared with the standard drug acarbose. Overall, the results demonstrated concentration-dependent antioxidant and antidiabetic efficacy of the biogenically synthesized iron oxide nanoparticles. Conclusion: The biogenic synthesis of iron oxide nanoparticles using H. umbellata L. is an eco-friendly and cost-effective approach. The synthesized nanoparticles exhibited excellent antioxidant and antidiabetic activities, highlighting their potential as promising candidates for the development of plant-based nanotherapeutics.